DIMENSIONS OF GENDER (IN) EQUALITY IN INDIA- A COMPARATIVE STUDY AMONG STATES OF INDIA - D. Jayarani; T. Sudha (PT. Radja Intercontinental Publishing, 2023)
Abstract This study takesup” Dimensions of Gender Equality in India.”While examining the dimensions the researchers compares the gender development index reports of states in India Gender equality-a driver for economic growth, matters in its own right,and as as pre requisite for the health and development of families and economies. The term gender equality has been on the corpet for the past two decades. The millennium development goals set gender equality and women empowerment at 3 rd place. Earlier women empowerment had been assessed interns of access to resources and later on moved to control over resources. The resources include physical resources. Fiscal resopurces, financial resources and intellectual resources. The term empowerment has been pronounced with the term empowerment after the millennium year. The post 2015 framework present a unique opportunity to build on the achievement of the millennium development goal, while also addressing that lag behind. The sustainable development goal also set Gender equality at fifth place. The reason is that Gender inequality persists everywhere and stagnates the progress of a country. The un equal treatment or perceptions of the individuals on the basis of gender have been witnessed not only in developing countries like India, but also in developed countries aswell. Gender related inequality in human well being is one of the most crucial issues in many states in India.The female dis advantage in survival is the important dimension that has drawn the attention of policy makers. InIndia the situation is not even among the states; Kearela has lesser discrimination while Odissa has higher discrimination. The sex ratio is also high in kerela which shows positive symptoms of women empowerment. Maharastra introduced property rights for women. Its percapita income is high compared to kerela but GDI is low. Female Education growth in kerela promotes gender equality.Has education alone dis appear inequalities is the million dollar question? Per capita income is not so high in kerela as compared to other southern states. The study examines gender equality on the basis of Gender Development Index, which measures gender gap in human development by accounting disparities between men and women in three dimensions of human develoipme3nt, a long and healthy life, knowledge and a decent standard of living. The global gender gap report places India at 135 out of 146 countries. India has moved from 140 to 135 from last year. Though India is moving towards one of the developed nations in the world, Gender inequality pulling its growth. Which factor is hindering the SGDs 5 the goal gender equality in India? The issue of gender inequality had been in the lime light in all academic conferences, seminars and symposiums. Why gender inequality prevails in higher degree in some states of India? What are the policy measures have to be pinned up? What are the measures to be added in those states? Any other indicators to be included along with HDI indicators? These are the research questions to be addressed. This paper is an attempt made by the researchers to address these issues